Words and structures refer in Alms Studying Languagal (Journal of the College of Education for Women, 2019)
Alms (or Zakat) is one of the Pillar of Islam and it was atask imposed onMuslims. Becomes of the importance of this task and its influence on the humanPsychic in particular and on the Society in general this study aims at Studying thewords that it refers to in the Holy Quran, At the beginning the researcher hasintroduced the words it refers to, and the significance of each in the Holy Quran andthe Speciality of each one of such words, then the Structures they donet have beenalso introduced, whether such structures are descriptive, adverbial or verbal.This wasintroduced in addition to explaining the influence of changing the Shape of suchwords in emphasizing the meaning and the influence of Portraiting style in bendingthe human psyche, such the Holy Quran tends to be used in different places to achievereligious and secular purposes.